ANALISIS KONSENTRASI DAN DEBIT SEDIMEN MELAYANG DI HILIR SUNGAI WANGGU KELURAHAN LALOLARA KOTA KENDARI - Laode Sabaruddin; La Baco Sudia; Hariani Hariani (Universitas Haluoleo, 2019)
The purpose of this study is to know the value of the concentration of sediment floating downstream of the Wanggu watershed. This research was conducted in Lower Wanggu River Kendari City, from Juli to Agustus 2019, this research was conducted in two stages, namely data collection in the field and laboratory tests. Retrieving data in the field in the form of river width, river depth, flow velocity and floating sediment samples. Research location at 2 observation stations, namely station I (deflection) and station I (Straight). Tests in labolatorum to get the sediment concentration values floating. The value of the floating sediment concentration is used to get sediment discharge drifting the river. The results of the research that has been done obtained the average concentration value at station I (deflection) the left part is 29,00 mg l-1, middle 30,67 mg l-1 and the right part of the river is 24,33 mg l-1, station II (straight), which is the left part of 25,67 mg l-1, the middle part is 21,67 33 mg l-1 and the right part is 27,00 33 mg l-1. The average discharge of sediment floated at station I left side 3,38x10-4 g day-1, middle 4,62x10-4 g day-1, and right side 2,77x10-4 g day-1. While at station II the left part is 3,76x10-4 g day-1, the middle part is 2,96x10-4 g day-1, and the right part is 3,19x10-4 g day-1.